The past and the present of citrus certification in Croatia - Skoric D.; Krajacic M.; Hartl D.; Gatin Z. (Proceedings of the Mediterranean research network on certification of citrus (MNCC): 1998-2001, 2002)
The main characteristics of the citrus industry in Croatia are given. The sanitary status is outlined as well as the perspectives for the establishment of the citrus certification program.
5. and 6. meeting of the CIHEAM Mediterranean Research Network on Certification of Citrus (MNCC), 2000/10/04-06, Algiers (Algeria) and 2001/10-11/26-01, Cairo (Egypt)